2015
DOI: 10.15282/jmes.8.2015.25.0147
|View full text |Cite
|
Sign up to set email alerts
|

Pure Polyurethane and Castor Oil Based Polyurethane: Synthesis and Characterization

Abstract: In this study, the physico-chemical properties of high performance polyurethane synthesized from poly propylene glycol (PPG) in comparison with a combination of PPG and castor oil, is studied using the in-situ polymerization technique. The variations in properties of both types of polyurethanes are evaluated by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD) and the thermogravimetric analysis (TGA) technique. Tensile strength properties were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…According to the SEM images, thermo‐H1 has a layered, flat, and homogenous structure, while thermo‐H2 has a spongy structure. The morphologies of thermo‐H1 and thermo‐H2 are consistent with similar studies performed by Neto and Alaa, respectively. In the literature, Wang et al .…”
Section: Resultssupporting
confidence: 90%
“…According to the SEM images, thermo‐H1 has a layered, flat, and homogenous structure, while thermo‐H2 has a spongy structure. The morphologies of thermo‐H1 and thermo‐H2 are consistent with similar studies performed by Neto and Alaa, respectively. In the literature, Wang et al .…”
Section: Resultssupporting
confidence: 90%
“…Figure 1(b) shows the main peak of HMDI which is the isocyanate peak at 2250 cm − 1 . Figure 1(c-f) represents all C4PU adsorbents with the disappearance of the isocyanate peak which showed that the polymerisation of C4PU has been successfully taken place [24,29]. The small broad IR band around 3500 − 3300 cm − 1 indicate the presence of N-H stretching vibrations from the amine group.…”
Section: Characterisations Of Adsorbentmentioning
confidence: 94%
“…The liquid components of LD40, Reprocell 300 and Reprocell 500 consist of a polyol resin and an isocyanate hardener (Alaa et al, 2015), with the resulting rigid foam a product of polymerisation, as two isocyanate groups per molecule chemically react with the polyol (Trovati et al, 2010). The mixing ratio was 1:1 by volume for all three foams.…”
Section: Polyurethane Foammentioning
confidence: 99%